Non-viral gene delivery to human mesenchymal stem cells using cationic liposomes - Mendes, Rui Daniel Martins Nunes (2010)
Tese de mestrado, Biologia (Biologia Molecular Humana), 2009, Universidade de Lisboa, Faculdade de Ciências